Bah humbug: Unexpected Christmas cards and the reciprocity norm. Issue 4 (3rd July 2016) - Meier, Brian P.
ABSTRACT: The reciprocity norm refers to the expectation that people will help those who helped them. A well-known study revealed that the norm is strong with Christmas cards, with 20% of people reciprocating a Christmas card received from a stranger. I attempted to conceptually replicate and extend this effect. In Study 1, 755 participants received a Christmas card supposedly from a more- versus less-similar stranger. The reciprocation rate was unexpectedly low (2%), which did not allow for a test of a similarity effect. Two potential reasons for this low rate were examined in Study 2 in which 494 participants reported their likelihood of reciprocating a Christmas card from a stranger as well as their felt suspicions/threat about the card and their frequency of e-mail use. Reciprocation likelihood was negatively correlated with perceived threat/suspicion and e-mail use. It appears that reciprocating a gift from a stranger in offline settings may be less likely than expected.